40 баллов, помогите(

40 баллов, помогите(
Гость
Ответ(ы) на вопрос:
Гость
2(x - 7) =  3 2x - 14 = 3 2x = 17 x = 8,5 5(x - 9) = - 2 5x - 45 = - 2 5x = 43 x = 8,6 4(x + 2) = 3 4x + 8 = 3  4x = -  5 x =  - 1,25 5(x + 5) = - 7 5x + 25 = - 7 5x = - 32 x = - 6,4 5(x + 9) = 9  5x + 45 = 9 5x = - 36 x = - 7,2 7(x - 1) = 3x 7x - 7 = 3x 7x - 3x = 7 4x = 7 x = 1,75 9(x + 7) = - x 9x + 63 = - x 9x + x = - 63 10x = - 63 x = - 6,3 5(x - 3) = 4x 5x - 15 = 4x 5x - 4x = 15 x = 15 4(x + 6) = x 4x + 24 = x 4x - x = - 24 3x = - 24 x = - 8 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы